The BJP's Welfare Schemes: Did They Make a Difference in the 2019 Elections?. (December 2019) - Deshpande, Rajeshwari; Tillin, Louise; Kailash, K.K.
In this article, we use data from the 2019 NES post-poll survey to assess the impact of BJP's welfare schemes on voting behaviour. We demonstrate that compared to earlier elections, voters are more likely to give credit to the central government as opposed to state governments or local politicians for welfare schemes. This centralization is especially the case for some of the BJP's new welfare programmes such as Ujjwala and the Jan Dhan Yojana . However, even earlier Congress-era schemes such as the Mahatma Gandhi National Rural Employment Guarantee Scheme and the Awas Yojana are now more associated with the central government. Schemes such as the Public Distribution System (PDS) and Old Age Pensions are still more likely to be associated with state governments. At the all-India level, we find some evidence that voters who received benefits under Ujjwala, Jan Dhan Yojana or Awas Yojana schemes were more likely to vote for the BJP, whereas recipients of pensions or MGNREGA were less likely to support the BJP.